BITCOIN SEBAGAI INSTRUMEN INVESTASI YANG MENGUNTUNGKAN - Achmad Wicaksono; Cynthia Eka Violita; Edita Rachma Kamila (Universitas Nahdlatul Ulama Sidoarjo, 2022)
This study was conducted to find out: (1) whether bitcoin is a profitable investment instrument; (2) how to make bitcoin a profitable investment instrument. This article was compiled using the “Library Research” approach where the data obtained will be analyzed in depth descriptively. The results of the study show that: (1) Bitcoin is a profitable investment instrument due to the limited supply of Bitcoin, which makes this instrument behave like Gold; (2) In order to become a profitable investment instrument, individuals can carry out mining activities to get Bitcoin prizes from miner applications and individuals can also carry out spot trading activities by taking advantage of the Bitcoin price difference when buying and selling so as to earn a profit.